Leviatan against COVID-19 - Lapuente, Víctor (Revista del CLAD Reforma y Democracia, 2022)
What is the relationship between States (governments and administrations) and the COVID-19 pandemic? This paper discusses the two potential causal relationships. On the one hand, how has the coronavirus affected and is affecting government and administrative structures? Are democratic systems and modernizing administrative reforms at risk? On the other hand, what effect do these governmental and administrative structures have on the better or worst management of the pandemic?
Keywords: State; Public Administration Structure; Administrative Reform; Democracy; Health Administration; Crisis Management; Infectious Deseases